Caring values in undergraduate nurse students: A qualitative longtitudinal study. (June 2019) - Rosser, Elizabeth A.; Scammell, Janet; Heaslip, Vanessa; White, Sara; Phillips, Jill; Cooper, Karen; Donaldson, Ian; Hemingway, Ann
Abstract: Introduction: Given the emerging evidence internationally of poor care within the healthcare sector, a recent report in the United Kingdom recommended the need for education to produce nurses who are prepared both intellectually and with compassion. Aim: This paper aims to understand the beliefs and values of caring, held by student nurses from entry to completion of their education programme. Methods: Using a prospective qualitative longtitudinal approach, two cohorts of nursing students (February 2013 and 2014) each following a different undergraduate curriculum (the February 2013, based on a philosophy of person-centred care and the February 2014, based on the philosophy of humanisation) were followed throughout their programme leading to Registration. Data were collected from February 2013 to February 2017 using individual interviews at commencement and completion of their programme with focus groups after their first placement and at the end of years one and two. Using purposive sampling, from February 2013, 12 commenced the study and five finished. From February 2014, 24 started, with nine completing. Findings: Data were analysed using thematic analysis with four themes emerging: i) Articulating the terms caring and dignity ii) Recognising the need for individualisation iii) Learning nursing and iv) Personal journey. Conclusion: Reporting on the final phase of this 5-phase study and on the brink of qualifying, both cohorts of students recognised the impact of their different curriculum and their exposure to the same educators who had embraced the humanisation philosophy. They each acknowledged just how they had changed as individuals and how determined they were to influence the quality of care.